2009
DOI: 10.1007/s10620-009-1049-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Tegaserod Treatment for Dysmotility-like Functional Dyspepsia: Results of Two Identical 1-year Cohort Studies

Abstract: The long-term safety profile of tegaserod in women with FD was consistent with that of short-term treatment and accompanied by improvements in HRQoL, work productivity and symptom relief. These long-term results add to the clinical experience with FD and support the potential value of a 5-HT(4) agonist in the management of FD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The OTE was used most recently in the acotiamide trial as a primary endpoint 25 and the tegaserod trial as a secondary endpoint. 26 The seven point Likert scale of OTE in both trials allocated 3 scales for measuring the degree of aggravation from slight to extreme. However, only few patients were reported as being aggravated.…”
Section: Discussionmentioning
confidence: 99%
“…The OTE was used most recently in the acotiamide trial as a primary endpoint 25 and the tegaserod trial as a secondary endpoint. 26 The seven point Likert scale of OTE in both trials allocated 3 scales for measuring the degree of aggravation from slight to extreme. However, only few patients were reported as being aggravated.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, tegaserod, a partial 5‐HT 4 agonist that was originally on the market for constipation‐predominant IBS and functional constipation, showed to be beneficial in the treatment of FD as well . A large randomised, placebo‐controlled study consisting of two identical trials showed a 4.6% improvement in days with satisfactory symptom relief after 6 weeks of tegaserod treatment (6 mg twice a day) over placebo.…”
Section: Current Treatment Options For Functional Dyspepsiamentioning
confidence: 99%
“…Despite this limitation, the remaining participants experienced multiple PRO symptom-based improvements. 27 Some of the heterogeneity in these study outcomes is likely attributable to the functional variability of individual serotonin agonists. Cisapride not only stimulates 5-HT 1-4 receptors, but also acts as a potent antagonist of both 5-HT 3 and human ether-a-go-gorelated gene (HERG) K + channels.…”
Section: Discussionmentioning
confidence: 99%